Local Production Systems and Alternative Food Networks in Amealco de Bonfil, Querétaro, Mexico - Bara, Claudia Rosina (2023)
Alternative Food Networks (AFN) emerged globally as competing movements and interconnections between alternative and small-scale food initiatives which counterpose the industrialized, globalized and mass consumption agri-food system. In Mexico, given the seriousness of the consequences that the industrial food system entails for people in the country, several alternative food initiatives have emerged that work in networks to promote local production systems and promote a transformation of this system from below. In the southern zone of the state of Querétaro, and specifically in the municipality of Amealco and its three main delegations, we analyze from a quantitative and qualitative methodology, what is the genetic richness of these indigenous communities in terms of edible plants and local crops and what role local production systems have, as well as the initiatives that integrate the AFN, in the construction of food sovereignty. For this purpose, we analyzed what local actors understand about food sovereignty from a territorial and cultural perspective, who are the actors that make up the AFN at the territorial level, how they interrelate and what are the requirements and challenges to consider walking towards food sovereignty.